Determining the viability of rental price to benchmark Islamic home financing products evidence from Malaysia - Mohd Yusof, Rosylin; Kassim, Salina; Majid , M. Shabri A.; Hamid, Zarinah (Emerald Group Publishing Limited, 2011)
Abstract - The purpose of this paper is to analyze the possibility of relying on the rental rate to price Islamic home financing product. Design/methodology/approach – By comparing two models consisting of either rental rate or lending rate (LR) and selected macroeconomic variables that could influence property value, the study focuses on the Malaysian data covering the period from 1990 to 2006. The study adopts several econometric time-series analysis, such as the autoregressive distributed lag estimates, bi-variate Granger causality, and multivariate causality based on the vector error-correction model. Findings – The study finds consistent evidence that the rental price (RP) is a better alternative than the LR to price Islamic home financing product. In particular, the rental rate is found to be resilient to short-term economic volatility, while in the long run, it is truly reflective of the economic fundamentals. Practical implications – This feature of the RP renders it as a fair pricing mechanism for the Islamic home financing product. Results of this study contribute towards finding an alternative benchmark for the Islamic home financing product which is currently using the conventional interest rate as its benchmark. Originality/value – To the best of the authors’ knowledge, the current study is the first of its kind which provides empirical evidence for the possibility of relying on the rental rate to price Islamic home financing product.